2012
DOI: 10.1371/journal.pone.0051120
|View full text |Cite
|
Sign up to set email alerts
|

The Activation Pattern of Blood Leukocytes in Head and Neck Squamous Cell Carcinoma Is Correlated to Survival

Abstract: Head and neck squamous cell carcinoma (HNSCC) is known to cause substantial immunosuppression. The present study was designed to characterize blood leukocyte activation in HNSCC and to investigate if the individual activation pattern could be related to tumor progress and survival. The leukocyte activation profile of HNSCC patients and healthy controls was assessed with flow cytometry. HNSCC patients displayed increased numbers of monocytes, neutrophils and total leukocytes as well as an enhanced neutrophil/ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
45
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 25 publications
8
45
0
3
Order By: Relevance
“…In another study on oral cavity cancer patients, it was observed that NLR increased in parallel with the advancement of clinical stage and T stage, but it was not significantly associated with survival (18). Furthermore, the opposite finding has also been reported, namely better survival associated with higher NLR in HNSCC patients, suggesting an antitumorigenic role of NLR (19). Rassouli et al (20) reported that NLR ≥4.2 predicts a higher recurrence rate (P<0.0001, log-rank test) and concluded that NLR may be used as an independent predictor of recurrence and survival.…”
Section: Discussionmentioning
confidence: 96%
“…In another study on oral cavity cancer patients, it was observed that NLR increased in parallel with the advancement of clinical stage and T stage, but it was not significantly associated with survival (18). Furthermore, the opposite finding has also been reported, namely better survival associated with higher NLR in HNSCC patients, suggesting an antitumorigenic role of NLR (19). Rassouli et al (20) reported that NLR ≥4.2 predicts a higher recurrence rate (P<0.0001, log-rank test) and concluded that NLR may be used as an independent predictor of recurrence and survival.…”
Section: Discussionmentioning
confidence: 96%
“…Another study reported that systemic inflammation as well as the numbers of monocytes, neutrophils and total leukocytes increased, and NLR enhanced in HNSCC patients (Millrud et al, 2012). Trellakis et al reported significantly higher NLR in HNSCC patients compared to controls (Trellakis et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of an elevated preoperative NLR has been validated as a marker of inflammation, and shown to have prognostic significance for a number of tumors (Jung et al, 2011;Idowu et al, 2012;Liu et al, 2013;Unal et al, 2013), including HNSCC (Trellakis et al, 2011;Millrud et al, 2012;Perisanidis et al, 2013;Rassouli et al, 2013;Tsai et al, 2013). It is considered as a marker of systemic inflammation which may predict worse prognosis by driving cancer cell proliferation through increasing the availability of growth factors, angiogenic factors and other pro-neoplastic signaling molecules (Hanahan and Weinberg, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In head and neck cancer, the role of tumor environment and inflammation has been discussed in the literature [8]. Evidence for an association of inflammation with prognosis in head and neck cancer patients has been presented recently ( [1,2,9,15,16,19,22] Grimm und Lazariotou [12], and references therein).…”
mentioning
confidence: 99%